Pre-discharge B-lines at bedside predicts 30-day and multiple 90-day hospital re-admission in patients admitted for acute decompensated heart failure. (3rd October 2022) - Zisis, G; Huynh, Q; Whitmore, K; Lay, M; Yang, Y; Carrington, M; Marwick, T
Abstract: Background: Inadequate decongestion at index admission for Acute Decompensation of Heart Failure (ADHF) is a common cause of adverse outcomes. A bedside 9-zone Lung and IVC ultrasound assessment (LUICA) may help to guide decongestion and reduce hospital readmission or mortality. Purpose: To identify predictors of multiple 90-day hospital representations or mortality based on a bedside handheld 9-zone LUICA volume assessment obtained by HF nurses. Methods: Patients admitted for ADHF, enrolled in the RISK-HF registry and undergoing pre-discharge LUICA, were assessed for 90-day readmission and/or mortality. The primary outcome of this observational report was prediction of multiple hospital representations based on pre-discharge volume status. The LUICA was performed with a hand-held ultrasound (HHU) device (Lumify, Philips) by trained HF-nurses. Functional capacity was measured with Duke Activity Status Index (DASI). Paired t-tests were used to compare mean differences. Logistic and linear regression were used to study relationships of outcomes with clinical characteristics. Cox regression was used to analyse time to repeated readmission or death. Analysis conducted with SPSS statistics V27 and STATA SE16. Results: Of 302 ADHF patients, 67 readmitted within 30-days (age 76±8.5; men, 60%; HFrEF; 44%) and 235 did not readmit within 30-days (age 72±14; 57% men; 52% HFrEF). Readmission occurred in older patients (p=0.05), with pre-discharge signs of residual congestion that was based on the number of b-lines (p<0.01) (Table 1). Pre-discharge B-lines were predictive of DAOOH (β −0.41, −0.6, −0.22, p<0.01) and of multiple 90-day hospital readmissions (β 0.03, 0.018, 0.05, p<0.01), independently of 30-day event risk score, number of readmissions the preceding 12 months and age at index admission (Table 2). Number of B-lines at discharge was also associated with repeated readmission or death (HR=1.02 [1.01, 1.04]) in time-to-event analysis, independent of any other factors. Conclusion: Pre-discharge residual congestion defined by the number B-lines increases the likelihood of multiple 90-day adverse outcomes. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): The University of MelbourneBaker Heart & Diabetes Institute